1995
DOI: 10.1063/1.360287
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of anisotropic stress around Si trenches by polarized Raman spectroscopy

Abstract: Polarized Raman spectra around trenches formed on (100) silicon wafers have been measured and it has been found that the peak frequency shift varies with the polarization configuration, suggesting that anisotropic stresses occur around the trenches. The different stress components have been calculated by the use of the polarization Raman technique and it was found that the stress distribution of each component approximately agrees with that of each component simulated by a finite element method. Polarized Rama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(33 citation statements)
references
References 7 publications
0
30
0
Order By: Relevance
“…[7][8][9] The residual stress in soft magnetic substrates, however, has hitherto been evaluated using an ellipsometer 10 which provides information closely associated with the electronic transition from the ground state to the excited one. However, the ellipsometer is not suitable for the evaluation of residual stress in rough surfaces, because this instrument necessarily requires the surface on which the laser beam is incident to be optically polished to a surface roughness of less than 0.8 m in an area of 2-10 mm.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9] The residual stress in soft magnetic substrates, however, has hitherto been evaluated using an ellipsometer 10 which provides information closely associated with the electronic transition from the ground state to the excited one. However, the ellipsometer is not suitable for the evaluation of residual stress in rough surfaces, because this instrument necessarily requires the surface on which the laser beam is incident to be optically polished to a surface roughness of less than 0.8 m in an area of 2-10 mm.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] In practice, Evans and Ushida 7 have shown that the linewidth of the Raman spectrum at 270 cm Ϫ1 in GaAs increases linearly with increasing particle size of polishing powder, and the broadening of the linewidth results from the microstructure disorder generated during polishing. We thus considered that a similar phenomenon is also observed in the Raman spectra of the soft magnetic Mn-Zn ferrite.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the forbidden optical phonon modes, the TO phonon modes, were excited even under the (001) Si backscattering geometry, using a high-numerical aperture (NA) liquid-immersion lens [22][23][24]. If all of the three optical phonon modes are detectable, the unknown three components of a stress tensor in Si can be obtained in theory [25][26][27][28][29][30][31][32][33][34][35]. The high-NA liquid-immersion Raman spectroscopy has great potential for measuring the complicated stress states in Si with high spatial resolution.…”
Section: Introductionmentioning
confidence: 99%
“…x 0 ¼ 1 ffiffi ffi 2 p ðÀ1; 1; 0Þ; y 0 ¼ ð0; 0; 1Þ; z 0 ¼ 1 ffiffi ffi 2 p ð1; 1; 0Þ; (7) and biaxial stress r 0 11 along the x 0 direction (horizontal direction) and r 0 22 along the y 0 direction (perpendicular direction) on a (110) face, Raman frequency shift Dx is written as 25,26 …”
Section: B Frequency Shift and Stress On A Cross-sectional Surfacementioning
confidence: 99%
“…The x 2 and x 1 modes are Raman active in the backscattering configuration from the (110) plane and observed in (x 0 , x 0 ) and (x 0 , y 0 ) configurations, respectively. [25][26][27][28] The notations (x 0 , x 0 ) and (x 0 , y 0 ) represent that the polarization of exciting light is along the x 0 direction while the polarization of scattered light is along the x 0 and y 0 directions, respectively. We choose the backscattering configuration from the (110) plane and the directions of the exciting and scattered lights are along the z 0 direction.…”
Section: B Frequency Shift and Stress On A Cross-sectional Surfacementioning
confidence: 99%